REKONSTRUKSI KERAJAAN GALUH ABAD VIII-XV - Lubis, Nina Herlina; Muhzin Z., Mumuh; Sofianto, Kunto; Mahzuni, Dade; Widyonugrohanto, Widyonugrohanto; Mulyadi, R.M.; Darsa, Undang Ahmad (Paramita: Historical Studies Journal, 2016)
The title of this research is Reconstruction of Galuh Kingdom in 8th-15thcentury. Issue that will be studied is how to unravel the location of the capital and palace shape of Galuh Kingdom. To answer the issue is used the historical method which consists of four steps, namely heuristic, criticism, interpretation, and historiography. Result of this research is that the existence of Galuh Kingdom is a history, not a myth. Historical sources which support the many arguments of its existence including inscriptions, foreign news, ancient manuscripts, social facts and mental facts. In addition, the life of its existence as long as eight centuries shows that Galuh Kingdom is not just existent but also strong because it is supported by a variety of solid and coherent system. Concerning about the location of capital and shape of the Kingdom , it still needs to explore further.Â Judul penelitian ini adalah Rekonstruksi Galuh Raya di abad ke-8-15. Masalah yang akan dipelajari adalah bagaimana mengungkap lokasi dari bentuk modal dan istana Kerajaan Galuh. Untuk menjawab masalah tersebut digunakan metode sejarah yang terdiri dari empat langkah, yaitu heuristik, kritik, interpretasi, dan historiografi. Hasil penelitian ini adalah bahwa keberadaan Kerajaan Galuh adalah sejarah, bukan mitos. Sumber-sumber sejarah yang mendukung banyak argumen keberadaannya termasuk prasasti, berita asing, naskah kuno, fakta sosial dan fakta mental. Selain itu, kehidupan keberadaannya selama delapan abad menunjukkan bahwa Kerajaan Galuh tidak hanya ada tapi juga kuat karena didukung oleh berbagai sistem yang solid dan koheren. Mengenai tentang lokasi ibukota dan bentuk Kerajaan, masih perlu untuk menjelajahi lebih lanjut.Â